Birt-Hogg-Dubé syndrome with simultaneous hyperplastic polyposis of the gastrointestinal tract: case report and review of the literature - Flávia Balsamo; Pedro Augusto Soffner Cardoso; Sergio Aparecido do Amaral Junior; Therésè Rachell Theodoro; Flavia de Sousa Gehrke; Maria Aparecida da Silva Pinhal; Bianca Bianco; Jaques Waisberg (BMC, 2020)
Abstract Background Birt-Hogg-Dubé syndrome (BHDS) is a rare autosomal dominant genodermatosis characterized by benign growth of the hair follicles, the presence of pulmonary cysts, spontaneous pneumothorax, and bilateral renal tumors that are usually hybrid oncocytic or multifocal chromophobe renal cell carcinoma. The diagnosis is confirmed by the presence of a pathogenic variant in the tumor suppressor folliculin (FLCN) gene mapped at 17p11.2. Although the dermatological lesions typical of BHDS are benign and only cause aesthetic concerns, and the pulmonary manifestations are controllable, the greater tendency of patients with this syndrome to present benign or malignant renal tumors, often bilateral and multifocal, makes the diagnosis of this syndrome important for the prognosis of the patients. The objective was to report the case of a patient with BHDS, without pulmonary manifestations and with hyperplastic polyposis of the gastrointestinal tract, and to perform a literature review. Case presentation A 60-year-old man complained of abdominal pain and diarrhoea for 2 months. Physical examination was normal except for the presence of normochromic papules in the frontal region of the face associated with hyperkeratotic and hyperchromic papules in the dorsal region. The excisional biopsies of the skin lesions indicated trichodiscomas. Esophagogastroduodenoscopy, enteroscopy, and colonoscopy showed the presence of hyperplastic polyps in the stomach, duodenum, jejunum, colon, and rectum. Computed tomography (CT) and magnetic resonance imaging (MRI) of the abdomen revealed multiple expansive solid lesions in both kidneys, with necrotic and calcified areas. Renal magnetic resonance angiography also showed a solid lesion in the right kidney measuring 5 cm in diameter and another solid lesion in the left kidney measuring 8 cm in diameter, both suggestive of renal angiomyolipoma. CT scans of the skull, chest, and temporal bones were normal. The genetic study revealed the presence of a variant of FLCN in the intron 13. Conclusions To the best of our knowledge, this is the first reported case of BHDS with the simultaneous finding of gastrointestinal hyperplastic polyposis, which may represent a possible phenotypic expression of this syndrome that has not yet been described.